Responsibilities of Business Actors to Protect Human Rights in Business Law - Sharon Dwi Yanti (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
This study discusses the responsibilities of business actors for the protection of human rights (HAM) in the context of business law in Indonesia. The approach used is normative juridical, focusing on the study of laws and regulations, scientific literature, journals, and legal documents related to the responsibilities of business actors to consumers, workers, society, and the environment. Primary data includes regulations such as Law Number 8 of 1999 concerning Consumer Protection and Presidential Regulation Number 60 of 2023 concerning the National Strategy for Business and Human Rights, while secondary data is obtained from journals, books, and scientific articles. The analysis technique applied is qualitative descriptive to interpret regulations and practices for the implementation of human rights in business. The results of the study show that business actors have multidimensional responsibilities, ranging from consumer protection, workers' rights, to responsibility for society and the environment, including in the digital era. Although the legal framework already exists, implementation on the ground faces obstacles such as regulatory limitations, lack of understanding of business actors, weak supervision, and conflicts between economic interests and human rights. The role of the state is proven to be strategic through the drafting of regulations, the enforcement of administrative, civil, and criminal sanctions, the supervision of consumer protection institutions, and the strengthening of corporate governance. This study concludes that human rights protection in Indonesian business law is comprehensive, but its effectiveness requires synergy between business actors, the state, supervisory institutions, and the community. The suggestions include improving human rights education, strengthening oversight mechanisms, improving corporate governance, adapting regulations to the digital era, and multi-stakeholder collaboration to ensure fair and sustainable business practices.